THE ROLE OF PERSONAL BRANDING IN MSME SUCCESS: A CASE OF EMERGING MARKETS IN ZAMBIA - Pethias Siame (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This study investigates the role of personal branding in the success of Micro, Small, and Medium Enterprises (MSMEs) within Zambia's emerging markets. Focusing on entrepreneurs in the urban center of Ndola, the research targeted MSME owners with a minimum of two years of operational experience. A purposive sampling technique was employed to select a sample of 30 MSMEs, ensuring representation across the service, retail, and manufacturing sectors. Grounded in Social Identity Theory, the study utilized semi-structured interviews to gather in-depth qualitative insights. The data were analyzed thematically to identify key patterns related to branding strategies and business performance. The findings indicate that personal branding significantly enhances business visibility and consumer trust, thereby fostering growth and creating a competitive advantage. Entrepreneurs who maintained consistent and authentic personal brands cultivated stronger customer loyalty and achieved improved financial outcomes. This research underscores the necessity for MSME owners in Zambia and similar emerging economies to adopt personal branding as a strategic imperative.